Research on CO dispersion of a vehicular exhaust plume using Lattice Boltzmann Method and Large Eddy Simulation. (May 2017) - Men, Yuzhuo; Lai, Yuyang; Dong, Suzhen; Du, Xin; Liu, Yihan
Highlights: A numerical approach has been developed for studying vehicle exhaust emission in urban road condition. Lattice Boltzmann Method and Large Eddy Turbulence model have been used for simulation. CO concentration and velocity distribution behind the exhaust plume has been investigated. The effectiveness of 3D simulation has been discussed in order to offer a better choice for engineer and architects. Abstract: The exhaust gas dispersion from the vehicles has a direct impact on human health, particularly on vehicle drivers, passengers, and people nearby. Because of the numerical implementation simplicity and well captured solution for fluid dynamics around multiple bodies, Lattice Boltzmann Method (LBM) has been adopted in lots of domains during the last two decades. This paper combines LBM together with Large Eddy Simulation (LES) turbulence model to study exhaust gas emission and dispersion characteristics. Carbon monoxide (CO) relative concentration and velocity distribution from a vehicular exhaust plume in the near-wake region is investigated for low and high idling driving conditions under different ambient wind speeds. Validation has been made to test the performance of gas simulation of the LBM-LES method in XFlow, after which 3D simulation of exhaust gas dispersion is considered, and the time-averaged CO relative concentration and velocity are analyzed. Results indicate that flow wake by ambient wind can affect the dispersion of exhaust gas. The exhaust gas moves downstream and spread to a wider range under higher ambient wind speed. While, the flow field becomes complicated due to the interflow effect when the wind speed and exhaust gas velocity are close, which enhances the dispersion characteristics of exhaust gas to a certain extent.